2017
DOI: 10.1111/ijau.12097
|View full text |Cite
|
Sign up to set email alerts
|

What drives and measures public sector internal audit effectiveness? Dependent and independent variables

Abstract: The effectiveness of the internal audit function is important to improve performance in the public sector. This study provides insight into the drivers and measures of internal audit effectiveness.The heads of the internal audit function, senior management of public institutions and chairpersons of the audit committee, within a South African public sector context, responded to a survey based on an extensive review of the internal audit function. Exploratory factor analysis was applied to facilitate the reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 27 publications
0
17
2
4
Order By: Relevance
“…() examined the effects of individual ethical orientation, independence threat and moral intensity on auditors’ ethical decision‐making process. Audit‐related internal controls include studies on audit committees (Böhm et al ., ), and internal audit (Coetzee and Erasmus, ). Studies on audit quality, for example, focused on the influence of regulation on audit quality (Knechel, ), and studies on audit fees include assessment of the relationships between business group affiliation, board quality and audit pricing (Johl et al ., ).…”
Section: Analyses Of Recent Accounting Publicationsmentioning
confidence: 99%
“…() examined the effects of individual ethical orientation, independence threat and moral intensity on auditors’ ethical decision‐making process. Audit‐related internal controls include studies on audit committees (Böhm et al ., ), and internal audit (Coetzee and Erasmus, ). Studies on audit quality, for example, focused on the influence of regulation on audit quality (Knechel, ), and studies on audit fees include assessment of the relationships between business group affiliation, board quality and audit pricing (Johl et al ., ).…”
Section: Analyses Of Recent Accounting Publicationsmentioning
confidence: 99%
“…One way that internal auditors contribute to corporate governance and ensure sustained performance is through their voice (Baker, Internal auditors are responsible for speaking up about potential problems (Khelil, Akrout, Hussainey, & Noubbigh, 2018;Wilson, McNellis, & Latham, 2018) and providing recommendations to improve internal control and risk management (Alzeban & Gwilliam, 2014;Arena & Sarens, 2015). Prior studies suggest that implementing recommendations suggested by internal auditors is an important indicator to evaluate the effectiveness of internal audit work (e.g., Alzeban & Gwilliam, 2014;Arena & Azzone, 2009;Coetzee & Erasmus, 2017;Soh & Martinov-Bennie, 2011).…”
Section: Internal Auditors' Voice In Environmental Issuesmentioning
confidence: 99%
“…The most significant determinant affecting the efficiency of the internal audit according to the authors is the competence level and the management strategy at the audit unit with reference to the audited entity's tasks. The auditor's competence level determines the adequate understanding of processes within the organisation, and the efficiency of internal audit function is assessed, among others, by analysing the reasons for rejecting post-audit recommendations (Coetzee and Erasmus, 2017). Some studies also emphasise internal audit efficiency indicators which also refer to internal audit function's capacity to enhance an organisation's performance by achieving relevant goals and tasks (Badara and Saidin, 2013;Bota-Avram and Palfi 2009;Endaya and Hanefah, 2013;Lenz, Sarens, and D'Silva, 2014;Arena and Jeppesen, 2016;Diamond, 2002;Van Gansberghe, 2005;Onumah and Krah, 2012).…”
Section: Assessment Of Internal Audit Efficiencymentioning
confidence: 99%